From anorexia nervosa to schizophrenia – a case report - Ziemiński, Rafał; Molas, Agnieszka; Morylowska-Topolska, Justyna; Gajewski, Jacek; Flis, Marta; Stelmach, Ewa; Karakuła-Juchnowicz, Hanna (Current Problems of Psychiatry, 2015)
Anorexia nervosa occurs more often in young women and is often comorbid with other mental disorders, e.g. depression and anxiety disorders. Cases of comorbidity with schizophrenia are relatively rare and have been described in the literature as case reports or case series. This article presents a case study of a patient who showed symptoms of both disorders coexisting in different proportions in the course of her illness. The prodromal period of schizophrenia lasted for 12 months. During the last three months of this period, after intensive dieting, the patient met all the criteria of anorexia nervosa mentioned in ICD-10: BMI = 16, she engaged in behaviors aimed at losing weight (dietary restrictions, food refusal, calorie countin, excessive exercise), she perceived herself as an obese person and suffered from amenorrhoea. After that period, the symptoms of anorexia coexisted with full-blown schizophrenia for another month. At that time, the symptoms of anorexia gradually started to subside, and psychotic symptoms began to resolve after long-term treatment with an antipsychotic (clozapine). When schizophrenia and anorexia coexist, the relationship between these two disorders may change over time, with the disorders coming to the fore at different times. Anorexia is sometimes a symptom of prodromal schizophrenia and may sometimes even prevail in the clinical picture. As our case report shows, coexistence of symptoms of anorexia and schizophrenia is a factor that hinders diagnosis and deteriorates the course of illness.